Análisis, diseño e implementación de un sistema de control y monitoreo de acceso y seguridad sobre una red ethernet utilizando chapas eléctricas y cámaras de video en los laboratorios del Colegio Remigio Geo Gómez Guerrero del cantón Huaquillas. - Jaramillo Merecí, Jonathan Xavier (2015)
Geo College Remigio Gomez Guerrero city of Huaquillas, had several problems and shortcomings with respect to safety and loss of time to access the computer labs. One of the main problems is that they had no computer and technological tools that allow a fast and efficient access of teachers, students and managers laboratories manner. With these antecedents mentioned was the need to develop and implement a monitoring and control system access and security on an Ethernet network using electrical sheets and video cameras, systematizing entry to computer labs. Mickrobasic was used for programming the pic that was used; Proteus well as for the circuit design and perform the respective simulations; Zend Framework also, which is an open framework for developing Web applications and services with PHP programming language code was used; AJAX is a web development technique for creating interactive applications running on the client, ie the users browser while asynchronous communication with the server in the background remains was used; also JAVA as driver-connector between the electronic circuit and the web application, as manager MySQL database used by the speed at the time of lookup data, and why is supported by a variety of operating systems . As a software development methodology for web system development methodology XP, which is based on continuous feedback between the client and the development team it was used. Therefore the development and implementation of the web system in the mentioned educational institution was improved security and access for teachers and students to computer labs optimized.